Prevalence and risk factors of obstetric fistula: implementation of a need-based preventive action plan in a South-eastern rural community of India - Dharitri Swain; Swayam Pragyan Parida; Saubhagya Kumar Jena; Mahasweta Das; Hrushikesh Das (BMC, 2020)
Abstract Background The study was conducted to estimate the prevalence and risk factors of obstetric fistula in the rural area of the south eastern community of India and the training of community health workers for its prevention. Methods A population-based cross-sectional analytical study was conducted in the south eastern rural community of India. A total of 3939 women were included in the study and Probability proportional to size sampling was used in the study. Frequency distribution and logistic regression were computed to analyse the data using STATA version 11.2. Results Out of 3939 participants interviewed, 23.7% women reported obstetric fistula symptoms whereas after clinical diagnosis and speculum examination the obstetric morbidity pattern was: Obstetric fistula 0.3%, stress urinary incontinence 20.0%, pelvic inflammatory diseases 1.2%, uterine prolapse 1.4% and urinary tract infection 3.8%. The awareness level of the rural women regarding the obstetric fistula was assessed by a structured knowledge questionnaire and found to be very poor, hence community based fistula training was implemented among community health workers as a health system based strategy for its prevention. Obstetric fistula found to be more prevalent among women of poor educational level, low socioeconomic status, less no of antenatal visits, delay in accessing the emergency obstetric care and prolonged labour (p ≤ 0.05). Conclusion Finding of the study indicated that the prevalence and risk of developing obstetric fistula was associated with less number of antenatal visits, prolonged labour, delay in timely intervention, delay in accessing emergency obstetric care and more number of movements from home to the delivery place. Finally, our study suggests that emphasis needs to be placed on training of community health workers to facilitate early screening for identification and referral of women with obstetric fistula.